Monetary Policy and Economic Growth in Nigeria: An Autoregressive Distributed Lag (ARDL) Analysis. - Ibrahim, Victoria Hauwa (Advances in Social Sciences Research Journal, 2019)
The study assessed the impact of monetary policy on economic growth in Nigeria. Three objectives guided the study. It employed quarterly data spanning 1986:Q1-2018:Q4, and used the Autoregressive Distributed Lag (ARDL) model, and the Granger causality test to carry out its empirical analysis and achieving its objectives. Findings from the study revealed that the monetary policy rate (MPR) had a positive impact on economic growth, but it was however not statistically significant. The broad money supply (M2) as a monetary policy instrument had a much more positive and highly statistically significant impact on economic growth in Nigeria. As such, the study recommended that the CBN should embark on a comprehensive monitoring of monetary instruments and aggregates and place less emphasis on inflation targeting (IT) alone. It is important to use other instruments which the central bank can control effectively like the broad money supply (M2) as it is more effective on the economy. Keywords: Monetary policy, Economic growth, Monetary Policy Rate, Broad Money Supply, New Consensus Macroeconomic.